The Semiotics of Belonging in the Novel “The Homeless” by Jabbour Al-Duwaihy - Ayoub, Nina Nabil (Dirasat: Human and Social Sciences, 2025)
Objectives: A narrative semiotic thematic study, which attempts, in a systematic reading based on structural narratives, to identify the issues formed, according to Jabbour Al-Duwaihi, in his novel “The Homeless.” by revealing the relationship between the space-time paper character and its affiliations, as part of the world of the novel, , and revealing the geographical spatial dimensions in the novel, and what it added on the pragmatic level, in highlighting the struggles and conflicts of belonging. Methods: Adopt the methodology of narrative semiotics, which benefited from discursive structuralism and opened up to other human sciences, including sociology, anthropology, and psychology. Results:. The semiotic approach is a methodological tool in the study of the text, through the tools employed on the narrative discourse, which enables understanding the semantic dimensions, and formulating the research as an integrative unit for the subject of study. It gives the recipient a level of knowledge, to penetrate the depth of the narrative experience Conclusions: The place is a tool of personal being and a means of recognizing its formative dimensions, and giving it a significance where the data of the outside world are transformed into internal human data. It reflects how cultures deal with it as part of their diversity, translating human, political, sectarian, existential and civilizational conflicts.